2015
DOI: 10.17705/1pais.07404
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Data Security Issues in Hospital Information Systems

Abstract: Nowadays, hospital information systems (HIS) provide real-time data and information in order to guide public health organizations especially in decision-making. The hospital information systems are integrated information systems designed to manage the administrative, financial and clinical tasks or aspects of a hospital. It plays an important role in planning, initiating, organizing and controlling the operations of the hospital, and a crucial role in providing quality healthcare services. The aims of this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…They searched and collected 101 papers, published in 72 journals of different disciplines. Masrom and Rahimly (2015) provided a deeper understanding of data security in hospital information systems, and contributed more knowledge to the field of healthcare industry. Masrom and Rahimly (2015) conducted a meta-analysis of 67 published studies and explored the influence of antecedents of trust in the e-service.…”
Section: Review Papersmentioning
confidence: 99%
See 2 more Smart Citations
“…They searched and collected 101 papers, published in 72 journals of different disciplines. Masrom and Rahimly (2015) provided a deeper understanding of data security in hospital information systems, and contributed more knowledge to the field of healthcare industry. Masrom and Rahimly (2015) conducted a meta-analysis of 67 published studies and explored the influence of antecedents of trust in the e-service.…”
Section: Review Papersmentioning
confidence: 99%
“…Masrom and Rahimly (2015) provided a deeper understanding of data security in hospital information systems, and contributed more knowledge to the field of healthcare industry. Masrom and Rahimly (2015) conducted a meta-analysis of 67 published studies and explored the influence of antecedents of trust in the e-service. The results showed that structural assurance (STA), reputation (REP), perceived usefulness (PU), system quality (SYQ), and service quality (SEQ), demonstrated the strongest effects on the antecedents of trust.…”
Section: Review Papersmentioning
confidence: 99%
See 1 more Smart Citation
“…A structure of healthcare information system [15] is shown in the below figure The various components present in figure 1 is described below Patients: Patient is used to gather, store and handle the information about patients. Laboratories: HIS manages the various lab related information like patient's medical testing including hematology, chemistry, immunology and microbiology.…”
Section: Introductionmentioning
confidence: 99%
“…Sony was also castigated for putting the personal and financial data of numerous customers at risk, with Sony UK fined $395,000 by the UK Information Commissioner for the breach of Data Protection Act (BBC, 2013). In the healthcare sector, which is the focus of this article information security is the most critical issue in the operation of information systems, as the data that is stored and processed is particularly sensitive (Masrom and Rahimly, 2015). It is clear that if sensitive medical information, such as mental health history; is accessed by unauthorised users, the subsequent infringement of patient privacy could have serious consequences for the individual concerned (Win, 2005).…”
Section: Introductionmentioning
confidence: 99%